1997
DOI: 10.1007/bf03015363
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine at induction reduces shivering after general anaesthesia

Abstract: Purpose: Postanaesthetic shivering occurs in 5-65% of patients. In addition to causing discomfort, it is associated with deleterious consequences. Our objective was to investigate the effect of 150/ag clonidine, at induction of anaesthesia, on perioperative core and peripheral temperature, incidence of postanaesthetic shivering and patients' perception of cold. Methods: Sixty ASA I or 2 patients scheduled for elective orthopaedic limb surgery were randomly allocated to group I, who received 150/Jg clonidine iv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
47
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 24 publications
(2 reference statements)
5
47
0
3
Order By: Relevance
“…The major finding was that there was no statistically significant difference between the efficacy of nefopam and clonidine in the prevention of postanaesthetic shivering, whereas both substances were beneficial when compared with the placebo. Postanaesthetic shivering is a common phenomenon and in our placebo group the incidence was 60%, a figure that is in accord with other studies [1,10,13]. Several drugs have been recommended [14][15][16][17][18][19][20], but the ideal drug for prevention and therapy has still not been found [9].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The major finding was that there was no statistically significant difference between the efficacy of nefopam and clonidine in the prevention of postanaesthetic shivering, whereas both substances were beneficial when compared with the placebo. Postanaesthetic shivering is a common phenomenon and in our placebo group the incidence was 60%, a figure that is in accord with other studies [1,10,13]. Several drugs have been recommended [14][15][16][17][18][19][20], but the ideal drug for prevention and therapy has still not been found [9].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, nefopam did not influence the recovery time, which is not surprising because nefopam has no sedative effects [22]. Several studies have shown a similar beneficial effect of clonidine for the treatment and prevention of shivering [1,5,10,17]. However, clonidine has well-known sedative properties and may reduce postanaesthetic shivering secondary to sedation of the patients [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations